Impact of substrate temperature on the structure and electrical performance of vacuum-deposited α, α′-DH5T oligothiophene thin films. Issue 116 (14th December 2016) - Mikayelyan, Eduard; Vladimirov, Ilja; Wesner, Daniel; Grodd, Linda; Rodygin, Alexander I.; Schönherr, Holger; Ponomarenko, Sergei A.; Pietsch, Ullrich; Ivanov, Dimitri A.; Grigorian, Souren
Abstract : Remarkable structural changes are reported for α, α′-DH5T oligomer thin films evaporated at different substrate temperatures and directly correlated with the electrical performance where the order of π–π stacking plays a crucial role. Abstract : The control over the structure and electrical performance of oligomer thin films is crucial for the functionality and reproducibility of organic devices. The effect of the substrate temperature during the vacuum evaporation of α, α'-dihexylquinquethiophene on the structure and morphology of the films was studied to understand its impact on charge transport in organic field-effect transistors (OFETs). Ordered multilayer structures were observed for the films deposited at different temperatures (36 °C, 60 °C, and 90 °C) onto SiO2 surfaces. On increasing the substrate temperature, a decrease in the monolayer thickness was observed, which is related to an increase in the tilt angle of the molecular long axis with respect to the surface normal direction. Atomic-force microscopy (AFM) revealed a more homogenous film morphology for the films deposited at 90 °C as compared to the densely packed island structures obtained at lower deposition temperatures. Interestingly, the films deposited at an intermediate temperature of 60 °C exhibited the highest crystallinity. An enhanced electrical performance of the OFET devices was also observed for the intermediate temperature of 60 °C, which correlates well with the improved molecular order due to π–π stacking interactions.